Expectativas formativas motivadoras del aprendizaje del inglés en estudiantes universitarios - Pérez-Lima, Ynés (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
The book is an adaptation of an investigation presented to the Universidad Andina Néstor Cáceres Velásquez that sought to analyze the formative expectations that motivate interest in learning English, comparing the different professional schools of the Universidad Nacional del Altiplano Puno. The study was cross-sectional-descriptive, considering all the students of the Universidad Nacional del Altiplano (18,941) as the population, applying a probabilistic sampling, obtaining a sample of 377 students from the different professional schools who have taken English courses. inside or outside the university. An adapted intrinsic and extrinsic motivation questionnaire of 15 items was elaborated, for the variable, the formative expectations of motivation of interest. After the hypothesis test, it was concluded that the training expectations that motivate interest in learning English, compared between the different professional schools, are regular.